Back to Basics: Measuring Economic Performance Using a Basic Needs Budget Approach - Seguino, Stephanie (Maine Policy Review, 1995)
Current measures of poverty have come under increasing scrutiny by policymakers and practitioners. Changes in family structure, labor force participation by women, and societal obligations such as child and eldercare call for more complex measurements of family need. Economist Stephanie Seguino focuses attention on the “basic needs budget,” a new approach to measuring poverty and family need. She proposes a set of criteria for developing a basic needs budget and suggests that the basic needs approach promises to provide a more accurate assessment of how our economic system is performing its basic task—that of ensuring an adequate production of resources and a fair distribution of those resources.